Detection and Treatment of Mental Illness Among Prison Inmates: A Validation of Mental Health Screening at Intake to Correctional Service of Canada - Martin, Michael (Université d'Ottawa / University of Ottawa, 2017)
Mental health screening is frequently recommended to facilitate earlier detection of mental illness in prisons. For this goal to be achieved: (1) the screening process must be accurate; (2) appropriate follow-up treatment must be provided; (3) the treatment must lead to improved outcomes. The current thesis aimed to evaluate mental health screening in relation to these three criteria by studying 13, 281 prisoners admitted to Correctional Service of Canada. Screening achieved comparable accuracy to tools that have been studied internationally and many inmates received at least some treatment. However, interruptions in treatment were frequent and long-term treatment was rare. There was weak evidence that treatment led to reduced rates of institutional incidents of suicide, self-harm, victimization and violence. While screening remains widely endorsed, further study of its impacts is needed to maximize its value. This could include considering alternatives to screening itself, or as follow-up for those who screen positive.
Keywords: Screening; Mental illness; Prison; Self-harm; Violence; Victimization